2021
DOI: 10.3389/pore.2021.622733
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Aggravates Tumor Growth in a Diffuse Gastric Cancer Xenograft Model

Abstract: Gastric cancer has the fifth-highest incidence rate and is the third leading cause of cancer-related deaths worldwide. The incidence of gastric cancer is higher in men than in women, but for the diffuse types of gastric cancer, the trend is opposite. Estrogen is considered the prime culprit behind these differences. Nevertheless, the action of estrogen in gastric cancers remains unclear. In this study, we investigated the effect of estrogen on diffuse-type gastric cancer. Human female diffuse gastric cancer SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This may simply have been due to the smaller number of gastric cancer patients in the female population. Additionally, considering that estrogen exerts a tumorigenic effect on diffuse-type gastric cancer, [30][31][32] and that diffuse-type gastric cancers are more prevalent in younger patients, [33] the elevated estrogen levels in young obese men may contribute to the stronger correlation between LDL-C and gastric cancer in young men.…”
Section: Discussionmentioning
confidence: 99%
“…This may simply have been due to the smaller number of gastric cancer patients in the female population. Additionally, considering that estrogen exerts a tumorigenic effect on diffuse-type gastric cancer, [30][31][32] and that diffuse-type gastric cancers are more prevalent in younger patients, [33] the elevated estrogen levels in young obese men may contribute to the stronger correlation between LDL-C and gastric cancer in young men.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Lee suggested that estrogen aggravates tumor progression in females with GC. 21 Thus, vitamin D and estrogen are suggested to be associated with GC prevalence and mortality, and further investigation is needed in relation to osteopenia.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Du et al reported that vitamin D may inhibit GC cell viability, proliferation, and metastasis and may inhibit Helicobacter pylori infection and Helicobacter‐associated GC 20 . Lee suggested that estrogen aggravates tumor progression in females with GC 21 . Thus, vitamin D and estrogen are suggested to be associated with GC prevalence and mortality, and further investigation is needed in relation to osteopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The estrogen receptor (ER) positive rate has been reported to be slightly higher in young females and in poorly differentiated gastric cancer. This may be the reason that poorly differentiated histological results have been found more common in female gastric cancer patients [ 30 , 35 , 94 , 95 ]. One study detailed the tumorigenic mechanism of estrogen in the development of ER α -positive diffuse-type gastric adenocarcinoma [ 94 ].…”
Section: Discussionmentioning
confidence: 99%